A heterogeneous rally effect for a corrupt president: partisanship, regional sentiment, and anxiety against a corruption scandal. Issue 8 (16th November 2020) - Chang, Kiyoung; Park, Jeeyoung
ABSTRACT: In this study, we focus on citizens' perceptions of external threats to account for their popular support for a corrupt leader. We argue that the public's perception of external threats may benefit a corrupt leader because the public tends to place a high value on the current leadership. Such a "rally effect" is stronger when a leader is more conservative. Additionally, we argue that the impact of an individual's perception of external threats on the punishment of a corrupt leader may be individual-specific. When we examine South Korean citizens' attitudes towards the 2016 − 2017 presidential scandal, we find that their concerns about either a local provocation or a massive war decrease the likelihood of an incumbent president being impeached. We also find that this impact of perceived threats is moderated by citizens' partisanship, regional backgrounds, and their anxiety concerning corruption scandals. Our empirical analysis suggests that the larger the pool of marginal disapprovers, the larger the potential rally for a president, and that citizens' feelings of anxiety against corruption weaken the rally effect.